Influence of refuge availability on the oviposition strategy of anachoretic and non-anachoretic aphidophagous ladybirds - António Onofre Soares; Marta Vale; Isabel Borges; Eric Lucas (BioControl, 2025)
Scymnus nubilus Mulsant and Coccinella undecimpunctata L. (Coleoptera: Coccinellidae) are two generalist aphidophagous predators abundant in herbaceous habitats. C. undecimpuctata , a larger species, lays its eggs in uncovered clusters, whereas S. nubilus , a tiny species , lays its eggs singly and, possibly, in concealed sites. Reproductive strategies in ladybirds seem to be adaptive, allowing the co-occurrence of both predators, apparently without interfering with each other. The aim of this study was to characterize the following oviposition strategies in S. nubilus and C. undecimpunctata : daily fecundity, effect of available sites on females’ fecundity, and circadian rhythmicity of oviposition. We hypothesize that the single-egg-laying strategist (1) is more dependent on the availability of concealed sites to oviposit and (2) lays eggs closer to aphid colonies. We found that different levels of site concealability allows S. nubilus to increase fecundity. Contrary to C. undecimpunctata , in the absence of a suitable substrate to conceal its eggs, S. nubilus females refrain ovipositing. S. nubilus prefers to hide their eggs beneath prey carcasses while C. undecimpunctata is less selective concerning the oviposition sites. S. nubilus dilutes its fecundity effort through more oviposition sites and events, while C. undecimpunctata requires one event to lay its clusters. Our results showed that the smaller ladybird is more dependent than the larger one on habitat structural complexity to maximize its fitness and that laying a single hidden egg mainly during the scotophase confers a potential adaptive advantage to increase fitness.

Can the ladybird predator Scymnus nubilus contribute to control of the aphid Aphis frangulae, a pest threatening the Macaronesia endemic Frangula azorica? - Isabel Borges; Patrícia Arruda; Roberto Meseguer; Virgilio Vieira; Gemma Pons-Solé; António Onofre Soares (BioControl, 2022)

Harmonia axyridis failed to establish in the Azores: the role of species richness, intraguild interactions and resource availability - António Onofre Soares; Alois Honěk; Zdenka Martinkova; Jiri Skuhrovec; Pedro Cardoso; Isabel Borges (BioControl, 2017)

Effect of temperature and prey in the biology of Scymnus subvillosus - Dalila Sebastião; Isabel Borges; António Onofre Soares (BioControl, 2015)

Harmonia axyridis: What will stop the invader? - António Onofre Soares; Isabel Borges; Paulo A. V. Borges; Geneviève Labrie; Éric Lucas (BioControl, 2008)